Algebra Questions

• Sep 10th 2010, 12:19 PM
Gronfeldt
Algebra Questions

a)
4/6
4/5

When I solved it the outcome was 5/6

b) - 72 - (-7)2

I got the outcome 0.

Can you help me?

My gratitude,

Gronfeldt
• Sep 10th 2010, 12:27 PM
yeKciM
Quote:

Originally Posted by Gronfeldt

a)
4/6
4/5

When I solved it the outcome was 5/6

b) - 72 - (-7)2

I got the outcome 0.

Can you help me?

My gratitude,

Gronfeldt

$\displaystyle \displaystyle \frac {\frac {4}{6}}{\frac {4}{5}} = \frac {4\cdot 5 }{4\cdot 6}= \frac {5}{6 }$
• Sep 10th 2010, 12:28 PM
bigwave
a) is
$\displaystyle \frac{\frac{4}{6}}{\frac{4}{5}} \Rightarrow \frac{4}{6}\times\frac{5}{4} \Rightarrow \frac{20}{24} \Rightarrow \frac{5}{6}$
• Sep 11th 2010, 04:42 AM
Gronfeldt
Quote:

Originally Posted by bigwave
a) is
$\displaystyle \frac{\frac{4}{6}}{\frac{4}{5}} \Rightarrow \frac{4}{6}\times\frac{5}{4} \Rightarrow \frac{20}{24} \Rightarrow \frac{5}{6}$

b) if you mean
$\displaystyle -\left(7\right)^2-\left(-7\right)^2 \Rightarrow -14-14 = 28$

otherwise what was given is correct.... you should us () with problems like this. or better yet latex

Thank you for your answer, but the ( ) weren't in the second problem. It was:

-7*2-/-(-7)*2
• Sep 11th 2010, 04:46 AM
Gronfeldt
Attachment 18886
Quote:

Originally Posted by Gronfeldt
Thank you for your answer, but the ( ) weren't in the second problem. It was:

-7*2-/-(-7)*2

• Sep 11th 2010, 05:02 AM
RHandford
Why is 7^2 14 and not 49?
• Sep 11th 2010, 09:33 AM
yeKciM
Quote:

Originally Posted by RHandford
Why is 7^2 14 and not 49?

heheheheheh :D:D:D

yes it is :D

lol but it's inconclusive is it $\displaystyle 7^2$ or the $\displaystyle 7\cdot 2$ and there one part of the brain sow it as $\displaystyle 7^2$ and while answering second part of the brain saw it as $\displaystyle 7\cdot 2$ so that's why that typo appear :D:D:D:D

$\displaystyle -7^2 - (-7)^2 = -49 - (+49) = -98$

$\displaystyle -7\cdot 2 - (-7)\cdot 2 = -14 - (-14) = 0$
• Sep 11th 2010, 10:44 AM
RHandford
yeKcIm

Sorry to be pedantic but:

$\displaystyle -7^2 - (-7)^2 = -49 - (+49) = 98$?

or

$\displaystyle -7^2 - (-7)^2 = -49 - (+49) = -98$

or

$\displaystyle -7^2 - (-7)^2 = -49 - (-49) = 0$

Sorry to be a pain (Worried)
• Sep 11th 2010, 11:08 AM
Unknown008
$\displaystyle -7^2 - (-7)^2 = -49 -(+49) = -49 - 49 = -98$

I'm surprised this thread has gone that many posts, but the solution so much time to be obtained...